2022
DOI: 10.1007/s11255-022-03329-8
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID-19 outcomes of non-dialysis dependent chronic kidney disease patients: a national, multicenter, controlled study

Abstract: Purpose Coronavirus disease 2019 (COVID-19) has a higher mortality in the presence of chronic kidney disease (CKD). However, there has not been much research in the literature concerning the outcomes of CKD patients in the post-COVID-19 period. We aimed to investigate the outcomes of CKD patients not receiving renal replacement therapy. Methods In this multicenter observational study, we included CKD patients with a GFR < 60 ml/min/1.73 m 2 wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
1
0
1
Order By: Relevance
“…In the present study, regarding history of ICU admission, MV, incidence of AKI and mortality were significantly different among the studied groups (P < 0.05), being higher in CKD 3 and not observed in CKD 1 suggesting the increased risk with advanced CKD stage. Karadag et al [9] study, in which 173 patients were included, showed that about 65% of patients had ICU admission, 20% had MV, and 2.9% suffered mortality. AKI development occurred in 54.8% of hospitalized patients, whereas 7.9% of patients needed dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, regarding history of ICU admission, MV, incidence of AKI and mortality were significantly different among the studied groups (P < 0.05), being higher in CKD 3 and not observed in CKD 1 suggesting the increased risk with advanced CKD stage. Karadag et al [9] study, in which 173 patients were included, showed that about 65% of patients had ICU admission, 20% had MV, and 2.9% suffered mortality. AKI development occurred in 54.8% of hospitalized patients, whereas 7.9% of patients needed dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…159 En pacientes con diagnóstico previo de enfermedad renal crónica antes de la COVID-19 se ha visto una mayor mortalidad y deterioro de la función renal a los 3 meses de seguimiento en comparación a sus homólogos. 160 Durante el seguimiento a largo plazo también se ha observado que la COVID-19 se asocia a un mayor riesgo de deterioro de la función renal (OR 4,60; IC 95% 2,10-10,08). 161 Un estudio que analizó una cohorte de más de 800.000 pacientes observó que la COVID-19 se asoció a los 6 meses a un mayor riesgo de fracaso renal, enfermedad renal terminal y mortalidad de todas las causas independientemente de la necesidad (HR ajustado 3,37; IC 95% 3,04-3,73) o no de ingreso (HR ajustado 1,15; IC 95% 1,07-1,23) hospitalario.…”
Section: Renalunclassified